UPAYA WORLD WILD FUND (WWF) DALAM MENGATASI OVERFISHING DI ROKAN HILIR PROVINSI RIAU - Arya Puspita Reza; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to explain the role of World Wild Fund for Nature (WWF) Indonesia especially WWF-Riau in preventing the overfishing problem in Rokan Hilir Riau Province. The actors are some from foreign fishermen, out-region fisherman, although Rokan Hilir’s fisherman. Beside that, they also used catch’s tool that was dangerous like trawl net which are explicit forbidden in regulation of Undang-Undang Perikanan Nomor 45 Tahun 2009 about the change of  Undang-Undang Nomor 31 Tahun 2004 that regulates the overfishing. The author used interest group level analyze and this research is using Constructivism perspective, international organization theory and also using concept of overfishing. WWF-Riau did an effort is by preventing the action of overfishing in Rokan Hilir sea where it shows that a minimum efforts of the local Government for the controls implementation, especially for preventing and correcting the overfishing control. Besides that, WWF-Riau is a facilitator between the local government of Rokan Hilir and the center government to tackle the overfishing in Rokan Hilir by the method of monitoring, surveillance, and controlling.Keywords: Overfishing, WWF-Riau, MSC, Rokan Hilir